An Evaluation Model Using Perceived User Technology Organization Fit Variable for Evaluating the Success of Information Systems - Muslimin, Imam; Hadi, Sasongko Pramono; Nugroho, Eko (Universitas Negeri Semarang, 2017)
In the information systems field, the fit between the components of information systems is a topic that has attracted the attention of many researchers. Various concepts of the fit such as Task-Technology Fit (TTF), Fit between Individuals, Tasks, and Technology (FITT), and Human Organization Technology Fit (HOT-Fit) are proposed and studied in various studies. In those various concept, the fit is one of the keys to the successful implementation and acceptance of information systems. Through a study of relevant literature, this study proposes a model consisting of human, organization, and technology characteristics, and adds the Perceived User Technology Organization Fit (PUTOF) variable as the initiated variable that influences the intention to use. In subsequent research, this model can be tested quantitatively with case studies of the information system implementation in an organization.